SURVEY QUESTION READ RECITE AND REVIEW (SQ4R) TO TEACH READING COMPREHENSION - Aditya, Dedek; Sari, Herni Mayang (EXCELLENCE: Journal of English and English Education, 2023)
This article is a general description about the use of Survey Question Read Recite and Review (SQ4R) to teach reading comprehension for students. Thus, it is hoped that teachers can have more choice in teaching reading comprehension to the students particularly in teaching and learning English.